(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This research examines mixed convection phenomena in stagnation point flow of a Casson hybrid nanofluid, exploring the synergistic effects of magnetic fields and thermal source/sink configurations. The study employs a water-based nanofluid system enhanced with copper (Cu) and aluminum oxide (Al2O3) nanoparticles flowing adjacent to a vertical surface. Using numerical methods with MATLAB’s shooting technique, we develop and solve a mathematical model that captures the complex interplay between electromagnetic forces and thermal gradients. The investigation advances current knowledge by simultaneously analyzing magnetic and thermal in fluences on hybrid nanofluid behavior, an underexplored area in contemporary research. Critical performance metrics such as velocity profiles, thermal distributions, skin friction, and Nusselt numbers are systematically evaluated. Results indicate that the hybrid nanofluid configuration achieves substantially improved thermal conductivity (up to 18% enhancement) compared to conventional fluids, with particular relevance to affordable and clean energy through optimized heat exchanger applications. The analysis of boundary layer dynamics provides fundamental insights into transport mechanisms, supporting Industry, Innovation and Infrastructure by informing next generation thermal management solutions. These findings offer significant potential for advancing energy-efficient technologies in power generation and industrial cooling systems, contributing to both responsible consumption and production through improved energy conversion efficiency.